MODERNIS VERSUS TRADISIONALIS DALAM PEMENUHAN KEBUTUHAN HIDUP: STUDI AYAT-AYAT TENTANG PRILAKU EKONOMI - Mawardi Mawardi (Program Pascasarjana IAIN Langsa, 2020)
Al-Qur'an, which is believed to be the word of Allah Most High, does not only regulate the way humans relate to God (hablum minallah) but also the human-human relationship (hablum minannas). The norms offered by the Koran in hablum minannas cover various aspects, including the economy. Economic values in the Koran are arranged in such a way so as not to cause social imbalances and gaps. Economic values in modern theory are seen from three aspects, namely reward, work ethic, and consumption. To determine the criteria for a developed economy, it is seen from these three aspects. In the Koran, these three aspects are emphasized for the attainment of prosperity and benefit so that the economic values described in the Koran are economies that are very relevant to be applied today.